FREQUENCY RESPONSE ANALYSIS FOR TRANSFORMERS - ABU HASSAN, MUHAMMAD HUSAINI (IRC, 2019)
To ensure transformers still in working condition, it must be tested with few tests. DGA (Dissolve Gas Analysis) test, insulation test, FDS (Frequency Dielectric Spectroscopy) test and etc[1]. As for knowing the condition inside the transformer especially on a transformer core and winding, testing the mechanical condition for both of it, we need FRA test. Frequency Response Analysis (FRA) or Sweep Frequency Response Analysis (SFRA) techniques have been gaining a lot of attention in analyzing the electrical winding and magnetic cores of power transformer throughout this decade[2]. As the test runs and being analyze, the localization of trending of faults is still in a depth of investigation. This research is focus on analyzing 5 testing method on transformer in finding and analyzing short circuit fault in the power transformer.